2012
DOI: 10.5812/jjm.2478
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbial Contamination and Physicochemical Condition of Public Swimming Pools in Kashan, Iran

Abstract: Most of the isolated fungi in the swimming pools can cause ear, eye and allergic diseases, therefore improvement the hygiene of swimming pools for control of microbial contaminations are recommended.Background: Swimming pools can transmit contagious diseases such as; fungal disease, otitis, conjunctivitis and amoebic meningoencephalitis. Objectives: The aim of this study was to determine the level of microbial contamination and the physicochemical condition of the swimming pools. Materials and Methods:In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
4
16
2
2
Order By: Relevance
“…Compared to other studies, TC was detected in 96.3 % of samples analyzed by Bekele and Leta (2014), while much lower figures were documented as 32.9 % by Papadopoulou et al (2008), 13.3 % by Martins et al (1995, in South America, and 9.0 % by Rasti et al (2012), in Iran. Their results underpin the importance of continuous monitoring and good maintenance of swimming pools.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Compared to other studies, TC was detected in 96.3 % of samples analyzed by Bekele and Leta (2014), while much lower figures were documented as 32.9 % by Papadopoulou et al (2008), 13.3 % by Martins et al (1995, in South America, and 9.0 % by Rasti et al (2012), in Iran. Their results underpin the importance of continuous monitoring and good maintenance of swimming pools.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings can explain the high bacterial counts and the high number of unacceptable samples. Other researchers supported these findings by reporting that the high prevalence of bacterial contamination was observed from indoor public swimming pools where the chlorine level was at its lowest level (Rasti et al 2012;Bilajac et al 2012;Fadaei and Amiri 2015).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Numerous authors worldwide have found low water quality in swimming pools , and emphasized the problem of mycological contamination and the risks associated with the presence of fungi in this environment. Yeast‐like fungi have also often been reported in swimming pools .…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have evaluated diverse aspects of purity in freshwater (Wurzbacher et al, 2010), seawater (Vogel et al, 2007), surface waters (Parveen et al, 2011) and across the whole water profile (Bis et al, 2013;Shearer et al, 2007), in outdoor Vogel et al, 2007) and indoor baths (Rasti et al, 2012), in drinking water (Biedunkiewicz and Schulz, 2012) and even in municipal fountains (Biedunkiewicz, 2009).…”
Section: Introductionmentioning
confidence: 99%